PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PERPAJAKAN, DAN PROGRAM PEMUTIHAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - M Hendri Yan Nyale; Shinta Dewi Condrowati (JURNAL LENTERA BISNIS, 2024)
The regional revenue heavily relies on vehicle taxes, playing a crucial role as one of the main pillars in generating significant income to support local development. Therefore, optimizing state revenue becomes crucial to achieve the government's expected targets. This research aims to examine the effects of taxpayer awareness, tax socialization efforts, and tax amnesty programs on the compliance level of vehicle taxpayers. The population focused on in this study consists of vehicle taxpayers registered at the SAMSAT office in Bogor City. Data collection utilized the simple random sampling method and Slovin's formula to obtain a sample size of 400 respondents. The type of data used is primary data analyzed through the use of a questionnaire with the assistance of SPSS software version 26, and the results were analyzed using a multiple linear regression analysis approach. The findings of this research prove that taxpayer awareness, tax socialization, and tax amnesty programs have a positive impact at a significance level of 5% (X1= 0.266, X2= 0.306, and X3= 0.318).